Sustainable Urban Corridors in Khartoum Case of Mohammed Najeeb Street - Omer A. Abuelzein (International Journal of Engineering and Management Research, 2021)
This article aims at measuring the sustainability of the streets of Khartoum using the Pedestrian Environmental Quality Index (P.E.Q.I.). This index has six categories: Intersection safety; traffic; street design; perceived safety; land use; and perceived walkability. Each category has several items. As a case study, Mohammed Najeeb main street is studied since it represents main streets in Khartoum. Results show that the sustainability standard of the studied street is below average (40%). Conclusions are written. And recommendations are drawn.